(untitled) (Ozone Therapy Global Journal, 2016)
Madrid June 11th, 2015 Excellences of the Spanish National Academy of Medicine Dear Prof. Velio Bocci, honorary chairman of ISCO3 Dear members ISCO3 Dear colleagues around the world With great pleasure I welcome you to the second meeting of the "Madrid Declaration on Ozone Therapy". The "Madrid Declaration", was born five years ago in this chamber, as a result of an initiative of Prof. Nabil Mawsouf, the big efforts of AEPROMO and the agreement of the main schools of ozone therapy in the world. In its first five years of life, ISCO3, faced setbacks and victories, but the latter far exceeded expectations. ISCO3 drafted the documents that have been crucial in the beginning of the change of the regulation of the practice of ozone therapy in the world. It has also created a scientific data base of free and global access and drafted documents that are crucial to the safe practice of this medical procedure. The first edition of the Madrid Declaration was translated into 12 languages ​​and was adopted as a guideline by 85% of the world associations of ozone therapists. The second edition of this document, is presented as a more comprehensive document from the scientific point of view. Its considering a "living" document that now includes much of the data provided by the scientific literature and recent clinical trials in the world. During its preparation many experts have been consulted who have contributed with their experiences to the new edition. In addition, a high number of proposals received from many ozone-therapists from around the world were considered. Also new in the second edition is the incorporation of the basic elements for the application of ozone in dentistry. Additionally, the second edition has an ISSN that will allow the document to be officially cited as a reference.